Hadith #2624 - Sunan Abi Dawud - Abu 'Abdur Rahman al-Salmi أبو عبد الرحمن السلمي; Ali ibn Abi Talib; Amr bin Marzuq al-Bahli عمرو بن مرزوق الباهلي; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zubayd bin al-Harith زبيد بن الحارث اليامي (Sunan Abi Dawud)
Ibn Juraij said “O ye who believe, Obey Allaah and obey the Apostle and those charged with authority amongst you.” This verse was revealed about ‘Abd Allaah bin Qais bin ‘Adi whom the Prophet (ﷺ) sent along with a detachment. Ya’la narrated it to me from Sa’id bin Jubair on the authority of Ibn ‘Abbas.
Grade: Sahih

Hadith #2650 - Sunan Abi Dawud - Abu 'Abdur Rahman al-Salmi أبو عبد الرحمن السلمي; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
‘Ali said “The Apostle of Allaah(ﷺ) sent me Al Zubair and Al Miqdad and said “Go till you come to the meadow of Khakh for there Is a woman there travelling on a Camel who has a letter which you must take from her. We went off racing one another on our horses till we came to the meadow and when we found the woman, we aid “Bring out the letter. She said “I have no letter”. I said “You must bring out the letter else we strip off your clothes”. She then brought it out from the tres
Grade: Sahih

Hadith #3250 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Hasan bin 'Ubaidullah الحسن بن عبيد الله بن عروة; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة (Sunan Abi Dawud)
” ‘Umar said: I swear by Allah, I never swore by it personally or reporting it from others.”
Grade: Sahih

Hadith #4692 - Sunan Abi Dawud - Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة (Sunan Abi Dawud)
Every people have Magians, and the Magians of this community are those who declare that there is no destination by Allah. If any one of them dies, do not attend his funeral, and if any one of them is ill, do not pay a sick visit to him. They are the partisans of the Antichrist (Dajjal), and Allah will surely join them with the Antichrist.
Grade: Da'if

Hadith #4748 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Alqama bin Mrthd علقمة بن مرثد; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
When the Prophet of Allah (ﷺ) was lifted to the heavens (for travelling) in Paradise, or as he said, a river whose banks were of transparent or hollowed pearls was presented to him. The angel who was with him struck it with his hand and took out musk. Muhammad (ﷺ) then asked the angel who was with him: What is this? He replied: It is al-Kawthar which Allah has given you.
Grade: Sahih

Hadith #5044 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة (Sunan Abi Dawud)
Some relative of Umm Salamah said: The bed of the Prophet (ﷺ) was set as a man is laid in his grave; the mosque was towards his head.
Grade: Da'if

Hadith #5045 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Fatr bin Khalifa فطر بن خليفة; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) wanted to go to sleep, he put his right hand under his cheek and would then say three times: O Allah, guard me from Thy punishment on the day when Thou raisest up Thy servants.
Grade: Sahih

Hadith #5046 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Yusuf al-Baykandi محمد بن يوسف البيكندي البخاري; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) said to me: When you go to your bed, perform ablution like the ablution for prayer, and then lie on your right side and say: O Allah I have handed over my face to thee, entrusted my affairs to thee, and committed my back to thee out of desire for and fear to thee. There is no refuge and no place of safety from thee except by having recource to thee. I believe in Thy Book which Thou hast sent down and in Thy prophet whom thou hast sent down. He said
Grade: Sahih